2010
DOI: 10.1152/ajpgi.00497.2009
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-like growth factors are more effective than progastrin in reversing proapoptotic effects of curcumin: critical role of p38MAPK

Abstract: Singh P, Sarkar S, Umar S, Rengifo-Cam W, Singh AP, Wood TG. Insulin-like growth factors are more effective than progastrin in reversing proapoptotic effects of curcumin: critical role of p38MAPK. Am J Physiol Gastrointest Liver Physiol 298: G551-G562, 2010. First published February 4, 2010 doi:10.1152/ajpgi.00497.2009.-Progastrin and insulin-like growth factors (IGFs) stimulate hyperproliferation of intestinal epithelial cells (IECs) via endocrine/paracrine routes; hyperproliferation is a known risk factor f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…3C), suggesting that progastrin did not regulate the ability of ALDH neg cells to generate ALDH high cells within this timeframe. To assess whether this lack of effect on ALDH neg cells was paralleled by a differential ability of progastrin to engage signaling in these cells, we analyzed the ability of progastrin to regulate the phosphorylation of p38MAPK, which plays a role in regulating CSC characteristics such as drug resistance (33) and is phosphorylated in response to progastrin (34,35 Endogenous progastrin depletion in ALDH high cells or treatment with recombinant progastrin, respectively, decreased or increased their sphere-forming ability (Fig. 3D and Supplementary Fig.…”
Section: Progastrin Promotes the Self-renewal Of Colorectal Cells In mentioning
confidence: 99%
“…3C), suggesting that progastrin did not regulate the ability of ALDH neg cells to generate ALDH high cells within this timeframe. To assess whether this lack of effect on ALDH neg cells was paralleled by a differential ability of progastrin to engage signaling in these cells, we analyzed the ability of progastrin to regulate the phosphorylation of p38MAPK, which plays a role in regulating CSC characteristics such as drug resistance (33) and is phosphorylated in response to progastrin (34,35 Endogenous progastrin depletion in ALDH high cells or treatment with recombinant progastrin, respectively, decreased or increased their sphere-forming ability (Fig. 3D and Supplementary Fig.…”
Section: Progastrin Promotes the Self-renewal Of Colorectal Cells In mentioning
confidence: 99%
“…Curcumin has potent anti-inflammatory, anti-bacterial and anti-cancer effects (10), but lacks solubility in aqueous solutions; bioavailable formulations have been developed (11) and are being examined in phaseI/II clinical trials (12, personal communications with Dr. Lawrence Helson). Curcumin is non-toxic at high doses (12g/day), and targets multiple oncogenic pathways (10,1214). However, pro-apoptotic effects of curcumin are attenuated by autocrine growth factors (14).…”
Section: Introductionmentioning
confidence: 99%
“…Curcumin is non-toxic at high doses (12g/day), and targets multiple oncogenic pathways (10,1214). However, pro-apoptotic effects of curcumin are attenuated by autocrine growth factors (14). Thus, sub-populations of cancer cells may escape inhibitory effects of curcumin; this concept was extended to CSCs in the current studies.…”
Section: Introductionmentioning
confidence: 99%
“…Experiments with mouse models of tumorogenesis have confirmed a critical role of Dclk1 in tumorigenesis, and as a CSC marker, as described below. It is important to note that overexpression of PG in either mature colonic epithelium (as in Fabp-PG mice) (19,(24)(25)(26) or in intestinal epithelial (IEC) cells (30), results in hyper proliferation of colonic crypts/cells, but does not cause neoplastic transformation (IEC-cells) or formation of colonic tumors (Fabp-PG mice) in the absence of AOM±DSS (19,(24)(25)(26)30). However, overexpression of PG in embryonic epithelial cells, allowed neoplastic transformation of the epithelial cells confirming hyper-sensitivity of multi-potent embryonic stem cells, unlike mature stem cells.…”
mentioning
confidence: 99%
“…We recently reported that a subset of DCLK1 + CSCs are resistant to inhibitory effects of potent chemopreventive agents such as curcumin (31), which may explain the failure of curcumin in clinical trials with cancer patients. Even though curcumin and several chemopreventive agents have been reported to attenuate multiple inflammatory and oncogenic pathways [discussed in (30,31)], for reasons unknown, a subset of DCLK1+ colon cancer cells, survive inhibitory effects of chemopreventive/ chemotherapeutic agents by undergoing autophagy, associated with survival rather than apoptosis (31). Downregulation of DCLK1 was required in combination with chemopreventive agents for eliminating CSCs and avoiding relapse (in terms of reformation of tumorospheres from colon cancer cells) (31).…”
mentioning
confidence: 99%